Longitudinal MRI evaluation of the efficacy of non-enhanced lung cancer brain metastases - Xian Zhang; Jun Yang; Hong Hu; Yong Wang; Zhenfeng Zhang; Jinhao lv; Junping Li (Scientific Reports, 2025)
Abstract Brain metastases (BM) are the most prevalent intracranial malignancies. Approximately 30–40% of cancer patients develop BM at some stage of their illness, presenting with a high incidence and poor prognosis. Our clinical findings indicate a significant disparity in the efficacy between non-enhanced and enhanced lung cancer BM. Therefore, the aim of this study is to conduct a longitudinal MRI evaluation of the therapeutic effect of non-enhanced lung cancer BM, thereby enabling improved efficacy prediction and more personalized treatment plans. We conducted a retrospective analysis of clinical and imaging data from 72 patients with lung cancer BM. Exclusion criteria included participants with a history of primary brain tumors, other malignancies, or neurological symptoms. We performed a longitudinal MRI evaluation of 8 patients with non-enhanced BM who met the eligibility criteria. The response to systemic therapy was locally assessed using the Neuro-Oncology response assessment criteria (RANO 2.0). A total of 8 patients were included in this study, comprising 4 cases of non-enhanced BM and 4 cases featuring both enhanced and non-enhanced BM. The median follow-up time for non-enhanced BM was 19 months, with a disease control rate of 50%. In contrast, the median progression-free follow-up time for enhanced BM was 35.5 months, yielding a disease control rate of 100%. After standardized treatment in accordance with clinical guidelines, patients with enhanced BM exhibited significantly better therapeutic outcomes than those with non-enhanced BM. Cases 1–4 demonstrated non-enhanced or mildly circular-enhanced lung cancer BM, with the sizes of all 4 lesions increasing by over 60% within approximately one year, indicating disease progression. In cases 5–8, each patient presented with two lesions: enhanced (Foci 1) and non-enhanced (Foci 2) BM. Comparative analysis of Foci 1 and Foci 2 revealed significantly weaker treatment responses in non-enhanced lesions (Patients 7–8), with Patient 5 exhibiting disease progression without any response. This study demonstrates that, following standardized treatment protocols aligned with clinical guidelines, the therapeutic effect of non-enhanced lung cancer BM is inferior to that of enhanced BM. Evaluating the enhancement type of lung cancer BM is essential for efficacy prediction and holds important implications for treatment guidance.